Inclusive Cancer Care: Rethinking Patients Living with HIV and Cancer - Corrigan, Kelsey L. (Oncologist, 2020)
HIV treatment is complex and has changed since the early years of the epidemic, especially as relates to treatment options for patients with cancer. This article focuses on disparities in cancer treatment care for people living with HIV.